Geochemical Appraisal of Chemical Weathering and Metal Contamination in Coastal Surface Sediments, Off Northwest Hainan Island, the Gulf of Tonkin - Liu, Dawei; Lin, Baozhi; Kandasamy, Selvaraj; Wang, Huawei; Liu, Qianqian; Zou, Wenbin; Zhu, Aimei; Zou, Jianjun; Lou, Jiann-Yuh; Shi, Xuefa (Frontiers in Marine Science, 2019)
Coastal sediments not only contain a majority of trace metals, but they also act as a source of dissolved metal ions to the overlying water column. Distinguishing the level of trace metal enrichment from the natural input in sediments is therefore important to determine the distribution and sources of land-derived detritus and pollutants in the coastal region. This study investigates fine (<63 µm) and bulk (<230 µm) fractions of surface sediments from the northwest coast of Hainan Island, South China, for sedimentological and geochemical parameters to evaluate the chemical weathering conditions of source rocks and geochemical processes controlling their distribution. Among seventeen major and trace elements investigated in this study, six elements (A1, Fe, Cr, Ni, V and Zn) varied spatially. Among four transects investigated, bulk and fine sediments from three northern transects (A, B and C) behave spatially almost similar, but the sediments from the southernmost transect (D) are characteristically different with higher contents of trace elements because of direct riverine influence with heavy mineral dominance. Range and mean values of weathering indexes, chemical index of alteration (CIA; 59–79 and 73) and chemical index of weathering (CIW; 78–91 and 85) as well as triangular plots of silicate weathering, revealed that sediments were derived from both granitic and basaltic rocks that have undergone moderate chemical weathering processes in the provenance. Normalization of trace elements to Al and the enrichment factor (EF) for fine and bulk sediments showed higher mean EF (>2) for As, Cd and Pb, suggesting that the sediments were likely enriched by these elements. A comparative study of trace metals concentrations and EF with other coastal regions of China however revealed that the study area is in a pristine environmental condition compared to other coastal regions of eastern China. Factor analysis identified three dominant sedimentological and geochemical associations, accounting for ~70% of total variance recognize terrigenous input, heavy mineral role and anthropogenic input in controlling the distribution of most elements in the study area.